Activité physique et fonctionnementcognitif chez les personnes âgées Physical Activity and Cognitive Functioning in the Elderly - BouzidBaa , Saliha (Milev Journal of Research and Studies, 2021)
Aging is characterized by a decline in cognitive and sensory-motor processes, but this decline is not the same for all individuals and certain factors, related to lifestyle, are likely to modulate its effects. One of these factors is regular physical activity. Indeed, with advancing age, maintaining regular physical activity is crucial in maintaining the functional capacities necessary for daily activities. This article aims to provide a review of the current state of research on the effects of physical activity on the cognitive functions of the elderly. After having briefly defined the key concepts, we will focus on the effects of physical activity on the brain and on the cognitive functions of the elderly through the presentation of the results of the studies carried out on this topic and then we will look at the types of activities that should be privileged and which are able to produce these positive and protective effects.